The complete plastid genome sequence of Picea jezoensis (Pinaceae: Piceoideae). (2nd September 2016) - Yang, Jong Cheol; Joo, Minjung; So, Soonku; Yi, Dong-Keun; Shin, Chang Ho; Lee, You-Mi; Choi, Kyung
Abstract: The nucleotide sequence of the complete chloroplast genome of P. jezoensis was completed. The total genome size was 124 146 bp, containing a pair of very short inverted repeats (IRa and IRb) of 422 bp, which were separated by large single copy (LSC) and small single copy (SSC) with 66 956 bp and 56 346 bp, respectively. The overall GC contents of the plastid genome were determined as 38.8%. One hundred fifteen genes including 68 peptide-encoding genes, 35 tRNA genes, four rRNA genes, six open-reading frames, and two pseudogenes were annotated. In these genes, 15 genes contained only one or two introns. Phylogenetic analyses using maximum likelihood (ML) methods were performed from fully sequenced Gymnosperms and other species of dataset composed of 69 protein-coding genes.